RELATIVE POWER DISTRIBUTIONS IN OMNIGUIDING PHOTONIC BAND-GAP FIBERS - Ibrahim, Abdel-Baset M. A.; Choudhury, Pankaj Kumar (E M W PUBLISHING, 2007)
Using Bloch formulations, an analysis is presented of the confinement of power in omniguiding photonic band-gap fibers of different dimensional values. Results are compared for four-layer and eight-layer fibers. Power peaks are observed that correspond to different propagation modes. Power patterns are found to be fairly smoothly matched at the different layer interfaces, which confirm the validity of the analytical approach.